Catalyst activation and influence of the oil matrix on the extractive oxidative desulfurization using aqueous polyoxometalate solutions and molecular oxygen - Bertleff, Benjamin; Claußnitzer, Johannes; Korth, Wolfgang; Wasserscheid, Peter; Jess, Andreas; Albert, Jakob (Energy & Fuels, 2018)
Our contribution describes the oxidative desulfurization of dibenzothiophene (DBT) from model oils using an aqueous H8PV5Mo7O40 (HPA-5) catalyst solution and molecular oxygen as the oxidant. In contrast to common oxidative desulfurization (ODS) protocols, the organic sulfur compound DBT is oxidized to water-soluble compounds, such as sulfuric acid (50–55%), sulfoacetic acid (20–25%), and sulfobenzoic acid (25–30%), which are extracted in situ into the aqueous catalyst phase. We describe the activating effect of oxalic acid on the ODS performance of the catalyst and propose a mechanism for the catalyst activation. Moreover, we report on the influence of various organic solvents, i.e., n-alkanes and aromatics, on the oxidative DBT removal. Remarkably, the rate of DBT oxidation and removal enhances with an increasing chain length of the alkane matrix, whereas aromatic compounds in the oil matrix inhibit the desulfurization rate. Moreover, we demonstrate that the aqueous catalyst phase can be reused at least 5 times without loss in catalytic performanc